Lipoprotein(a) Management: Pharmacological and Apheretic Treatment - Hanssen, Ruth; Gouni-Berthold, Ioanna (Current Medicinal Chemistry, 2017)
Lipoprotein (a) [Lp(a)] is a low-density lipoprotein (LDL)-like particle with an additional apolipoprotein, apolipoprotein (a), [apo(a)] attached to apolipoprotein B. Recent epidemiologic and Mendelian randomization studies have provided evidence that Lp(a) is causally related to the pathogenesis of atherosclerosis and cardiovascular disease (CVD). The risk association between Lp(a) concentrations and CVD is still controversial but seems to be continuous and without an obvious threshold Lp(a) level. Circulating concentrations of Lp(a) are genetically determined; desirable levels are < 50 mg/dl. A plasma concentration of 60 mg/dl is associated with an odds ratio for coronary heart disease of about 1.5 after adjustment for other cardiovascular risk factors. Extended-release niacin is an option for decreasing elevated Lp(a) levels (by 20-30%) but it is often poorly tolerated. Dietary measures, exercise and lipid-lowering drugs such as statins and ezetimibe are without significant effect. In patients with severe progressive CVD and very high Lp(a) levels, lipoprotein apheresis can decrease Lp(a) concentrations. The method is expensive and impractical for most patients and its feasibility depends mainly on the healthcare reimbursement system. Since no established treatment reduces Lp(a) without influencing other lipoproteins, there has been no trial that evaluated whether decreasing Lp(a) concentrations translates to clinical benefits. Recently, an antisense oligonucleotide against apo(a), IONIS-APO(a)Rx, has been shown to selectively decrease Lp(a) by almost 80%. A phase 2 study with this drug has been completed in late 2015 and results are expected to be published soon.
Keywords: cardiovascular disease